Multiple-dose pharmacokinetics of cefonicid in patients with impaired renal function. - Phelps, R T (1986)
The pharmacokinetics of multiple-dose administration of cefonicid to patients with normal and impaired renal function were studied by using high-performance liquid chromatography to measure serial serum and urine concentrations. Eighteen patients received an initial dose of 15 mg/kg intravenously over 12 min plus two or three subsequent modified doses at intervals of 24 to 72 h, depending upon the degree of renal impairment. Six patients chronically requiring hemodialysis and 12 nondialysis subjects (creatinine clearance, 10 to 80 ml/min per 1.73 m2) were studied. The concentrations of cefonicid in serum after the initial dose were best described by an open two-compartment model. The elimination half-life of cefonicid ranged between 5.5 and 84.9 h. Mean peak and trough concentrations in serum for all patients were 178.2 +/- 29.3 micrograms/ml (plus or minus standard deviation) and 39.0 +/- 17.5 micrograms/ml, respectively. Trough concentrations were higher in patients requiring hemodialysis than in nondialysis subjects, but the difference was clinically insignificant. The renal clearance/plasma clearance ratio of cefonicid was linearly related to creatinine clearance and decreased with impaired renal function. Therefore, nonrenal mechanisms of elimination become more important as renal function declines. Since cefonicid concentrations were within the therapeutic range for nearly all dosing intervals, we conclude that the guidelines used for dosage reduction and interval prolongation in this study result in therapeutically adequate concentrations in serum and, at the same time, result in no significant drug accumulation.